Vortex-assisted switchable liquid-liquid microextraction for the preconcentration of cadmium in environmental samples prior to its determination with flame atomic absorption spectrometry - Firat, Merve; Bodur, Suleyman; Tisli, Busra; Ozlu, Cansu; Chormey, Dotse Selali; Turak, Fatma; Bakirdere, Sezgin (SPRINGER, 2018)
In this study, a switchable solvent was used to preconcentrate trace amounts of Cd from aqueous solution for its determination by flame atomic absorption spectrometry (FAAS). Protonation of N,N-dimethylbenzylamine by dry ice (solid CO2) made it water soluble, and addition of sodium hydroxide converted it back to its original nonionic state for phase separation and subsequent extraction of Cd. A slotted quartz tube (SQT) was attached to the flame burner head to increase the residence time of Cd atoms in the light path. Under the optimum conditions, limits of detection and quantification were determined as 0.7 and 2.6 mu g L-1, respectively. Low relative standard deviations calculated from seven replicate measurements of the lowest concentration indicated high precision. Accuracy of the developed method was checked by using a standard reference material (SRM 1633c). Spiked recovery tests were also performed on lake water and wastewater samples at different concentrations to check the applicability of the developed method, and the results obtained (90-103%) established high recovery.
Keywords: Cd; FAAS; SQT; Switchable solvent extraction; PHASE MICROEXTRACTION; TRACE LEVELS; EXTRACTION; NICKEL; WATER; LEAD; SEA; Environmental Sciences & Ecology